Carrie - King, Stephen, 1947- (New York : Anchor Books, a division of Random House, Inc., 2011)
Carrie, an odd girl who is ostracized at school, has the power of telekinesis and after being harassed by her fellow students begins to exact revenge with violence.
Adult
Adult.
850
Keywords: Psychokinesis -- Fiction; Bullying -- Fiction; Revenge -- Fiction; Good and evil -- Fiction; Psychokinesis -- Fiction; Bullies -- Fiction; Revenge -- Fiction; Good and evil -- Fiction; Horror fiction; Horror fiction